The negative impact of smartphone usage on nursing students: An integrative literature review. (July 2021) - Ramjan, Lucie M.; Salamonson, Yenna; Batt, Sharryn; Kong, Ariana; McGrath, Belinda; Richards, Gina; Roach, David; Wall, Peter; Crawford, Ruth
Abstract: Background: Smartphones are ubiquitous, and for some, an indispensable companion. In nursing education curricula and clinical healthcare settings, smartphones have the potential to augment student learning. Nursing students report significant benefits to smartphone use, which extend beyond learning, to include enhanced communication, clinical decision making and evidence-based practice. Despite these benefits, little is known about the negative impact of smartphones on student learning. Objectives: This integrative review aimed to synthesise findings from published research that referred to the detrimental direct or indirect effect of smartphone usage on nursing students. Design: The integrative review was guided by the five-stage approach as conceptualised by Whittemore and Knafl (2005) . Methods: Seven electronic databases were systematically searched in consultation with a university librarian (CINAHL Plus, Ovid Medline ALL, Nursing and Allied Health Database, PsycINFO, PubMed, Scopus and ERIC) using a combination of key search terms and medical subject headings. A total of 646 articles were retrieved, and following removal of duplicates, screening of titles and abstracts, a final 27 articles met the inclusion criteria for this review. Results: Studies in the review originated from Korea ( n  = 7), Turkey ( n  = 6), India ( n  = 4), Spain ( n  = 3), USA ( n  = 2), Spain/Portugal ( n  = 1), Iran ( n  = 1), France ( n  = 1), Canada ( n  = 1) and Egypt ( n  = 1). Personal smartphone use was reported to be a distraction within clinical and classroom learning, and considered as uncivil, and compromised professionalism. Frequently, smartphones were used for entertainment (e.g. social networking) rather than professional purposes. The studies identified a concerning level of nomophobia and smartphone addiction among nursing students that caused stress and anxiety, and adversely affected sleep, learning and academic performance. Recommendations were proposed for smartphone policies. Conclusions: Excessive smartphones use among nursing students may adversely affect physical and mental health and potentially impact on student learning within the classroom and clinical environment. Educators should consider the implementation of policies or guidance for the responsible use of smartphones by nursing students whilst in the classroom setting and during clinical placement, to mitigate the potential negative impact on health and academic performance.